Servant Leadership and Followership : Examining the Impact on Workplace Behaviour - Davis, Crystal J. (Palgrave Macmillan, 2017)
"Providing a deeper understanding of leadership, followership theory, and the follower as servant leader, this book provides employee and follower perspectives of servant leadership in the workplace. The collection brings together both empirical and conceptual research from around the globe to illustrate how the leader is seen through the lens of the follower. Topics discussed include organizational performance, empowerment, competency models, diversity in the workplace, and social roles and stereotypes. With contributions from a range of skilled authors, Servant Leadership and Followership not only provides an overview of servant leadership, but also offers insightful ways for organizations to adapt and progress in line with the shifting moral demands of today's workplace."-- Provided by publisher.
Keywords: Servant leadership.; Followership.; elektronické knihy; electronic books